THE INFLUENCE OF AUDIT COMPETENCY AND WORK EXPERIENCE ON COMPUTER-ASSISTED AUDIT TECHNIQUES AND THEIR IMPACT ON AUDIT QUALITY AT THE BPK REPRESENTATIVE OFFICE OF NORTH SUMATRA PROVINCE - Rizqi Anggraini; Eka Nurmala Sari; Irfan (CV. Radja Publika, 2025)
This study aims to determine, analyze and test the effect of auditor competence and work experience on computer-assisted audit techniques and their impact on audit quality. This type of research is quantitative. This research was conducted using a survey method by distributing questionnaires to auditors working at BPK representative office in North Sumatra Province. Sampling using saturated sampling with a total of 95 respondents. Data analysis was performed using path analysis techniques by using the SPSS program. The results of this research to show that work experience affects computer-assisted audit techniques, computer-assisted audit techniques affect audit quality, auditor competence affects audit quality, work experience affects audit quality. However, the auditor competence has no effect on computer-assisted audit techniques. The results of the Sobel test also prove that work experience affects audit quality through computer-assisted audit techniques but the auditor competence does not affect audit quality through computer-assisted audit techniques. These results conclude that computer-assisted audit techniques can mediate (intervening) work experience on audit quality.